Calibration method of wave polarization data obtained by KAGUYA/WFC. Issue 9 (27th September 2016) - Goto, Yoshitaka; Uda, Kazuaki; Kasahara, Yoshiya; Hashimoto, Kozo
Abstract: A calibration method for wave polarization data obtained by waveform capture (WFC) instrument on a lunar orbiter KAGUYA is introduced. In order to obtain correct polarizations of plasma waves observed by KAGUYA, it is necessary to remove the difference of onboard delays between two orthogonal channels of the receiver. For that purpose, we use observation data of natural waves instead of onboard calibration signals which were not available due to a technical problem during the mission period. KAGUYA often observed auroral kilometric radiation (AKR) from the Earth, which had polarizations. The phase differences are determined by using AKR data obtained under a specific condition. As a result, the polarization data are calibrated with a sufficient accuracy. The proposed calibration method is not specialized for the KAGUYA data but it can be applied to wave data obtained with similar types of receivers in future missions. Key Points: A lunar orbiter KAGUYA observed polarizations of various waves around the Moon Calibration of the polarization is conducted using observation data of auroral kilometric radiation